Effect of early weaning on the growth performance of Boran and Boran X Friesian bull calves - Tegegne, Azage; Mukasa-Mugerwa, E.; Ketema, H. (1990)
Evaluates the growth performance of calves born to Boran cows and weaned at either six or eight months. Early weaned calves were further divided to either receive supplementary feed until eight months of age or serve as controls. There was no significant differences between Boran and crossbred calves in terms of birth weight, actual weaning weight, adjusted weaning weight, and pre-weaning average daily gain. However, average daily gain was significantly greater in early-weaned calves than in late weaned calves. Early weaned calves were significantly heavier at eight months than Boran calves while Boran calves lost weight between six & eight months of age. Daily gain of supplemented calves was altogether greater than that of unsupplemented calves.